2011
DOI: 10.3189/002214311798043861
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal evolution of water contributions to discharge from a Greenland outlet glacier: insight from a new isotope-mixing model

Abstract: ABSTRACT. The Greenland ice sheet (GrIS) subglacial hydrological system may undergo a seasonal evolution, with significant geophysical and biogeochemical implications. We present results from a new isotope-mixing model to quantify the relative contributions of surface snow, glacial ice and delayed flow to the bulk meltwater discharge from a small ($5 km 2 ) land-terminating GrIS outlet glacier during melt onset (May) and at peak melt (July Rn and the stable water isotopes. Applying this model to the bulk subgl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
63
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 56 publications
4
63
2
1
Order By: Relevance
“…Hence, by its nature, distributed system meltwater should acquire significantly higher 222 Rn activities than meltwater that flows through open channels. Discrete 222 Rn measurements in small glacial watersheds have been used to infer the transition from distributed to channelized drainage (Kies et al, 2011;Bhatia et al, 2011;Kies et al, 2015). This paper expands upon these earlier studies by examining the utility of long term continuous 222 Rn measurements in the proglacial river of a large GrIS outlet glacier during the spring and summer of 2011 and 2012.…”
Section: Introductionmentioning
confidence: 91%
“…Hence, by its nature, distributed system meltwater should acquire significantly higher 222 Rn activities than meltwater that flows through open channels. Discrete 222 Rn measurements in small glacial watersheds have been used to infer the transition from distributed to channelized drainage (Kies et al, 2011;Bhatia et al, 2011;Kies et al, 2015). This paper expands upon these earlier studies by examining the utility of long term continuous 222 Rn measurements in the proglacial river of a large GrIS outlet glacier during the spring and summer of 2011 and 2012.…”
Section: Introductionmentioning
confidence: 91%
“…Stable isotopes provide evidence for assessing plant water sources according to their variations caused by equilibrium and kinetic isotopic fractionation mechanisms (Orlowski et al, 2016a;Haverd et al, 2011;Zhao et al, 2013;Bhatia et al, 2011). Several studies (Liu et al, 2013;Mathieu and Bariac, 1996;Allison and Barnes, 1985) have shown that transpiration do not cause isotopic fractionation of soil water.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of meltwater discharged from the Greenland ice sheet first drains contact (Bhatia et al, 2011). In the present study, discharge was also measured at the were substantially higher than a filter process blank (see below) such that we were able to 111 utilize these samples for Fe analyses.…”
mentioning
confidence: 67%
“…For example, at Haut 554 Glacier d'Arolla, a similarly-sized Swiss Alps glacier with a schist-gneiss-amphibolite 555 bedrock, sulfate concentrations in the bulk runoff are typically less than 200 µeq/L, but 556 borehole waters sampled at the bed could have a sulfate concentrations up to 1200 µeq/L 557 (Tranter et al, 2002). An exception to dilute sulfate concentrations in the 'N' glacier 558 runoff was the May 21 st sample which drained the lowest measured discharge waters with 559 the largest modeled delayed (basal) flow component (Bhatia et al, 2011). The sulfate 560 concentration in this sample was 929 µeq/L, thus hinting that some component of the 'N' 561 subglacial hydrological system may drain regions that support microbially-mediated 562 anoxic sulfide oxidation.…”
Section: Introduction 1mentioning
confidence: 98%
See 1 more Smart Citation